2012
DOI: 10.1136/gutjnl-2011-301574
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation and incidence of inflammatory bowel disease among US women

Abstract: Objective Geographical variation in the incidence of Crohn’s disease (CD) and ulcerative colitis (UC) according to the latitude of residence has been reported in Europe. However, there are no comparable data in the USA. The incidence of CD and UC in relation to latitude was assessed in a geographically diverse population of women enrolled in two large prospective studies in the USA. Design A prospective study was undertaken of women enrolled in the Nurses’ Health Study I (NHS) in 1976 and in the NHS II in 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
146
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(167 citation statements)
references
References 25 publications
18
146
0
3
Order By: Relevance
“…Two separate published analyses, based on data from women who participated in the Nurses' Health studies in the USA, support this association between higher latitude and higher incidence of IBD (25,27) . Khalili et al reported a significant increase in incidence of both CD and UC according to more northerly latitude of residence (25) . The authors further analysed the latitude of residence across a number of time points and found the strongest association at age 30 years.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 89%
See 3 more Smart Citations
“…Two separate published analyses, based on data from women who participated in the Nurses' Health studies in the USA, support this association between higher latitude and higher incidence of IBD (25,27) . Khalili et al reported a significant increase in incidence of both CD and UC according to more northerly latitude of residence (25) . The authors further analysed the latitude of residence across a number of time points and found the strongest association at age 30 years.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 89%
“…The exact cause of IBD remains unknown; however, the disease is thought to result from a complex interaction between immunological, genetic and environmental factors. Vitamin D status is one such postulated environmental risk factor (24)(25)(26) . Epidemiological studies show a geographic variation in the incidence of IBD, with a higher incidence in countries of more northern latitudes, mirroring sunlight patterns and likely to reflect vitamin D levels.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiologically, we know that the incidence of IBD is higher in countries in which ultraviolet exposure is lower or which are more distant from the equator-i.e., countries with a high prevalence of vitamin D defi ciency ( 8 ). Studies examining the individual level ultraviolet exposure based on small-area analysis of postal codes or within larger regions in the country have demonstrated a similar gradient in the incidence of IBD that correlates inversely with predicted levels of vitamin D insufficiency ( 9 ). We also know that vitamin D defi ciency is common in those with IBD, perhaps more so than in the general population, and that this is apparent even in newly diagnosed patients ( 10 ), arguing against such defi ciency being solely a consequence of prolonged disease.…”
mentioning
confidence: 99%